2009
DOI: 10.1027/1015-5759.25.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Rational and Intuitive Thinking Styles

Abstract: Theories of dual cognition assume two distinguishable information processing styles: rational and intuitive. We discuss how the concepts of rationality and intuition are used in these theories, and the relations of these two thinking styles to personality characteristics. With the Rational-Experiential Inventory (REI; Pacini & Epstein, 1999 ), a questionnaire that assesses personal preferences for thinking either rationally or intuitively, we found clear evidence for the independence of the two thinking st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
126
4
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 29 publications
18
126
4
5
Order By: Relevance
“…Studies of different age groups (Marks et al, 2008;Pacini & Epstein, 1999) and across different cultures (Witteman et al, 2009) confirm the existence of the two thinking styles and their predictive validity. Therefore, it might be expected that preferred thinking styles may have a similar pattern of heritability to personality traits.…”
mentioning
confidence: 90%
“…Studies of different age groups (Marks et al, 2008;Pacini & Epstein, 1999) and across different cultures (Witteman et al, 2009) confirm the existence of the two thinking styles and their predictive validity. Therefore, it might be expected that preferred thinking styles may have a similar pattern of heritability to personality traits.…”
mentioning
confidence: 90%
“…Witteman et al (2009) reported a satisfactory fit of the model comprising two related factors (RMSEA = .07 (90% IC = .064, .068), NFI = .77, SMR = .054, GFI = .83). Of 20 rational items, 19 items showed a factor loading higher than .40, and 19 of 20 experiential items showed a factor loading between .37 and .69.…”
mentioning
confidence: 98%
“…Instead, experiential items loaded on two factors that differ in the form of writing, positive and negative. Other studies have also found that two components account for about 33% of the total variance together (Björklund & Backstrom, 2008;Witteman, van den Bercken, Claes, & Godoy, 2009). However, Björklund and Backstrom (2008), when examining the four-factor solution did not find the expected structure of two sub-dimensions (skill and preference) in the rational and experiential dimensions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The REI-40 has been found to be reliable (Cronbach's alpha 0.74-0.91) and consistent. 8,10,[14][15][16] It involves 40 questions that are scored on a five-point Likert scale from "Definitely False" to "Definitely True." Twenty of these questions assess each thinking style (rational or experiential), of which 10 assess favourability towards a style and 10 assess ability to use a style.…”
Section: Study Protocolmentioning
confidence: 99%